1994
DOI: 10.1212/wnl.44.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizures associated with intrathecal baclofen application

Abstract: We report the clinical and EEG findings in three patients presenting with seizures associated with intrathecal baclofen application for treatment of spasticity. All patients had a history of traumatic brain injury, while one patient also suffered a spinal cord injury. Two patients experienced their first seizure following intrathecal baclofen test bolus injection. Another patient had convulsions on two occasions: following postoperative baclofen dose adjustment, and after sleep deprivation. Structural brain di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
4

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 0 publications
0
40
0
4
Order By: Relevance
“…Although GABA B Rs are mediators of slow inhibitory effects of GABA in the brain, a series of experimental and clinical observations have shown that application of the canonical agonist baclofen can induce seizures in animal models, as well as patients (15,16,29,30). To address a possible mechanism, we performed in vivo experiments in a mouse model of TLE and found that baclofen acts in a dose-dependent manner: at a high dose (10 mg/kg), baclofen reduces network excitability and oscillatory activity, consistent with its inhibitory actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although GABA B Rs are mediators of slow inhibitory effects of GABA in the brain, a series of experimental and clinical observations have shown that application of the canonical agonist baclofen can induce seizures in animal models, as well as patients (15,16,29,30). To address a possible mechanism, we performed in vivo experiments in a mouse model of TLE and found that baclofen acts in a dose-dependent manner: at a high dose (10 mg/kg), baclofen reduces network excitability and oscillatory activity, consistent with its inhibitory actions.…”
Section: Discussionmentioning
confidence: 99%
“…GABA B Rs are expected to have an overall antiepileptic effect, and indeed, the receptor KO animals show an epileptic phenotype (14). However, there is also evidence that the receptor agonist baclofen can induce seizures in patients after intrathecal application (15,16). The picture is further complicated by the fact that GABA B R expression can be altered in both epileptic patients, e.g., in mesial temporal lobe epilepsy (mTLE) (17), and animal models (18).…”
mentioning
confidence: 99%
“…This is possible, though the brevity and frequency of episodes in these cases would be unusual for TGA (Bartsch & Butler, 2013). Baclofen is capable of provoking both generalised and focal seizures, making an epileptic mechanism plausible (Han, Cortez, & Snead, 2012;Kofler et al, 1994). The lack of associated symptoms of epilepsy, EEG abnormalities or response to anticonvulsant treatment, argue somewhat against this diagnosis in CS' case.…”
Section: What Caused the Episodes Of Transient Amnesia?mentioning
confidence: 95%
“…It can be given orally, or, in more severe cases, by infusion from an implanted pump into the CSF (Hsieh & Penn, 2006). This targets the drug on the desired spinal site of action, but the normal bulk flow of CSF toward the brain sometimes leads to CNS side-effects (Kofler, Kronenberg, Rifici, Saltuari, & Bauer, 1994). In overdose, intrathecal baclofen can cause coma and status epilepticus (Nugent, Katz, & Little, 1986;Saltuari, Marosi, Kofler, & Bauer, 1992).…”
mentioning
confidence: 99%
“…There are reports of new-onset seizures after introduction of the IT baclofen, but nearly all describe patients after significant head trauma. 43 In fact, Buonaguro et al 44 recently reported a reduced seizure rate of 13% in 150 children studied, with two patients worsening and one experiencing new onset ictus. Additionally, there are reports of scoliosis exacerbation after IT baclofen.…”
Section: Patient Selection For Intrathecal Baclofenmentioning
confidence: 97%